Wanda Maximoff’s Grieving Process and Her Imaginary World in WandaVision Series: A Lacanian Perspective - Davita Soimatul Fauziah; Ali Mustofa (Interference: Journal of Language, Literature, and Linguistics, 2022)
Abstract. This study aimed at investigating further stages experienced by someone who is going through the process of grieving from the loss of a loved one forever, namely Wanda Maximoff and its relation with her world of her imagination in Matt Shakman's "WandaVision" series. This study applied Lacanian theory, namely the mirror stage and the five stages of grief theory, from Elizabeth Kubler Ross to elaborate the data.  The data obtained is a collection of scenes and dialogues in each episodes of this series.The results show that Wanda Maximoff experiences stages of grief after the death of her lover, namely Vision. However, her grief was so deep that she created her imaginary world, West View. According to Lacan theory, this arises because of the imaginary, which is Wanda's hidden desire. The world is Wanda's dream that contradicts the reality she faced. The imagination is usually experienced unconsciously by someone going through a mourning period. Therefore, the analysis of the stage of grief in Wanda's character can help us better understand our emotions.  Keywords: Grief, Imaginary, Lacanian, WandaVision.